Introduction to Soft Matter: Synthetic and Biological Self-Assembling Materials - Hamley, Ian W (West Sessex : John Wiley, 2007)
This book provides an introduction to this exciting and relatively new subject with chapters covering natural and synthetic polymers, colloids, surfactants and liquid crystals highlighting the many and varied applications of these materials. Written by an expert in the field, this book will be an essential reference for people working in both industry and academia and will aid in understanding of this increasingly popular topic. Contains a new chapter on biological soft matter Newly edited and updated chapters including updated coverage of recent aspects of polymer science. Contain problems at the end of each chapter to facilitate understanding
Includes Index 317-328p.
Keywords: Colloids; Liquid crystals; Micelles; Polymers